Analysis of the variation of injury patterns in people who have experienced sexual violence - Soularto, Dirwan Suryo; Nanda Ayu Prastiwi, Nugraha (Institute of Computer Science (IOCS), 2023)
Establishing sexual violence can be a complex process due to the lack of witnesses other than the perpetrator and victim. So, law enforcers rely on medical practitioners to find medical evidence, such as physical damage to the victim's body. The objective of this study is to establish the characteristics of different injury patterns in individuals who have experienced sexual violence. This study is a comprehensive descriptive analysis of medical records and visum et repertum (VeR) data obtained from five hospitals in Yogyakarta, Indonesia. A total of 84 cases met both the inclusion and exclusion criteria. The findings indicated that 60.7% of victims did not experience recurring incidents of sexual violence. In most cases, the perpetrator typically had a preexisting relationship with the victim (81%), and 25% of the victims underwent a medical examination more than 45 days after the incident. The predominant injuries observed on the victim's body were contusions, with 52.6% occurring in the chest region and 26.3% in the upper extremities. The prevailing genital injury observed was an old rupture of the hymen. There was no apparent relationship between the injuries that occurred outside the genital and genitoanal area. Moreover, a significant correlation was found between the proximity of the perpetrator to the victim.